Strategy for Strengthening Pancasila Values through Education to Face the Challenges of the Modern Era - Prastisyar Arkaan Kautsar (Konsultan Jurnal Ilmiah Indonesia, 2026)
This research aims to understand the relevance of Pancasila values ​​in the modern era and the challenges they face in national and state life. In the modern era marked by globalization and digitalization, Pancasila values ​​face challenges such as political polarization and a national identity crisis, although they remain the foundation of Indonesian unity. This research aims to analyze the relevance of Pancasila and its implementation strategies in national and state life through a literature review. The method involved a journal search using the keywords